Empowering Elderly Through Health Counseling to Increase Self-Acceptance and Elderly Activities - Hasanah, Nur; Padoli, Padoli; Suprianto, Suprianto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Physical and psychological changes in the elderly will affect their social adjustment abilities, for better or worse.High feelings of inferiority in the elderly will result in the elderly having low self-acceptance. The aim of this community service is to increase self-acceptance and activities of the elderly at the UPT Pelayanan Sosial Tresna Werdha Magetan. This community service was carried out from May 2022 to October 2022, in the form of health education about self-awareness and self-acceptance of the elderly. Health education was carried out using lecture and demonstration methods. The target audience for the counseling is 50 elderly people at the UPT Pelayanan Sosial Tresna Werdha Magetan. Health education was carried out orderly and smoothly according to plan. Elderly attendance reached 100% on the first day and 90% on the second day. The elderly were very cooperative, enthusiastic and actively participated in the counseling until it was finished and most of the elderly were able to carry out the self-hypnosis techniques that were trained. This health education can increase the self-awareness and self-acceptance of the elderly, which can be seen from the increase in the willingness and ability of the elderly to take part in social activities that are routinely held in nursing homes. Considering that self-hypnosis techniques are easy for elderly people to do themselves anywhere and at any time, it is recommended that elderly people do it regularly as therapy to improve the self-awareness and self-acceptance.